(untitled) (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2021)
This research is motivated by the number of Islamic education institutions in Indonesia that have not been able to implement integrated curriculum management in their educational institutions. Even so, some of them have started to develop and implement an integrative curriculum, one of which is MAN Insan Cendekia Pekalongan. This research is a field research with a qualitative approach, which aims to describe the management strategies of the integrative curriculum structure in MAN Insan Cendekia Pekalongan. Data collection was carried out by participatory observation, documentation and interviews with madrasah managers, teachers and students. Data analysis using data reduction techniques, data display then drawing conclusions and data verification. The results of this study indicate that, the integrated curriculum structure management strategy in MAN Insan Cendekia Pekalongan uses integrative galactic management curriculum techniques.